ANALISIS METODE CAMELS SEBAGAI ALAT UKUR EFEKTIVITAS KINERJA KEUANGAN PERBANKAN SYARIAH - Maulidatun Nikmah; Jeni Susyanti; Achmad Agus Priyono (UNIVERSITAS ISLAM MALANG, 2019)
ABSTRACT The purpose of this research is to analyze the financial performance of Islamic banking using the CAMELS method. This research is classified as quantitative research. Documentation is used by researchers as a data collection technique. The data used in this research is secondary data. The population and sample in this study were 9 Islamic banking companies registered at Bank Indonesia. The variables used in the CAMELS method are CAR (Capital Adequacy Ratio), NPL (Non Performing Loan), NPM (Net Profit Margin), ROA (Return On Asset), BOPO (Operating Expenses and Operating Income), LDR (Loan Deposit Ratio) , and IER (Interest Expense Ratio). Testing the data in this study using discriminant analysis. The results of this study note that the variables that prove to be the most dominant in distinguishing the status of the bank's health are BOPO variables. While the variables CAR, NPL, NPM, ROA, LDR, and IER are smaller than BOPO. BOPO has a more important meaning for other variables in forming a discriminant function.Keywords: CAMELS Method, Bank Health, and Discriminant Analysis